DESIGN OF ENGLISH LEARNING BASED ON LIVE STREAMING OF DIGITAL ERA IN COVID-19 - Faidah Yusuf (JURNAL EDUSCIENCE (JES), 2021)
The important of this paper is live streaming using gadget as a learning English speaking in Covid-19 era relying on the internet and utilizing the social media platform facebook. This research is a descriptive qualitative study, used on 40 students. The result identified seven steps to create a Facebook group and learning tool to produce lecture units, student activity sheets, and student worksheets. The analysis of this study discussed the seven steps of English learning design of English learning devices based on live streaming Facebook; 1) starting from creating an online Facebook group, 2) entering the design phase or design begins with entering or clicking on the facebook application, and then create a class facebook group, 3) write the name of the group of courses taught in class, 4) click type closed groups, 5) click to find the link, 6) click "Share" to see the class group link, 7) click copy to the clipboard. Student responses to learning are good, thus this learning design can be applied in the classroom. so the result of this design steps, They can practice learning English, especially speaking in live streaming video, which is a new activity for students on social media, namely Facebook.